1) True
2) False
3) True
4) False
5) False
Analyzing the table and the function g(x)= -12(1/3)^x
We can see that:
The y-intercept is given when x=0
So, (0, -12) and :
![\begin{gathered} g(x)=-12((1)/(3))^x \\ g(0)=-12((1)/(3))^0 \\ g(0)=-12(1) \\ g(0)\text{ =-12} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wkpn903yr6kp94t0uzn1va24w9ba4r1jr9.png)
1) So both functions have the same y-intercept (y= -12).
Checking the second option:
![\begin{gathered} g(0)\text{ =-12} \\ g(1)=-12((1)/(3))^1,\text{ g(1)=-4} \\ g(2)=-12((1)/(3))^2=-(12)/(9)=-(4)/(3) \\ g(3)\text{ =-0.44} \\ g(4)=-0.142 \\ g(-1)\text{ =-}36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ikee00788ltprv1lmx2lxo4irwhqzwrnw9.png)
2)So, as we can see both functions are increasing on this interval ([0,4], but not in every interval of x. False, since g(x) is a decreasing function.
3) For f(x) and g(x) this is true. since according to this graph we can see that the end behavior
Notice that as x approaches -∞, f(x) approaches -∞ as well as g(x). True
4) That's false too since both functions approach different values as x approaches infinity.
5) No, they do not have the same x-intercept. f(x), has x=2, and g(x) no.
![\begin{gathered} g(x)=-12((1)/(3))^x^{}_{} \\ 0=-12((1)/(3))^x \\ (0)/(-12)=-(12)/(-12)((1)/(3))^x \\ 0=((1)/(3))^x \\ No\text{ solution in R} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lu7wpf5t1s5yjiztzd0e2g53l47pl13who.png)